ESTABLISHING A CONCEPTUAL MODEL FOR ASSESSING PROJECT MANAGEMENT MATURITY IN INDUSTRIAL COMPANIES - Spalek, Seweryn (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
The number of projects undertaken by companies nowadays is significant. Therefore, there is a need to establish processes in the company supporting and increasing project management efficacy. In order to achieve this, the companies need to know how good they are at organizational project management, taking into consideration different perspectives. Knowing their strengths and weaknesses, they are able to improve their activities in challenging areas. In view of the critical literature review and interviews with chosen companies, the article proposes a conceptual model for assessing project management maturity in industrial companies. The model is based on four assessment areas. Three of them (human resources, methods & tools, and environment) represent the traditional approach to maturity measurement, whilst the fourth, knowledge management, represents a new approach to the topic. The model was tested in over 100 companies in the machinery industry to verify its practical application and establish valid results of implementation, which have not been previously explored.